Debt and firm value in Malaysia: A panel threshold regression analysis - Ahmad, Abd Halim @ Hamilton; Abdullah, Nur Adiana Hiau (2011)
There have been number of studies discussing the optimal level of capital structure since the seminal work of Modigliani and Miller (1958).In this study, we examine whether an optimal level of debt exist at which a firm could maximize its value.An advanced panel threshold regression model by Hansen (1999) is employed to test the effect of debt ratio on the firm value among Malaysian listed firms from 2005 to 2009. The findings from this study show that additional debt beyond the threshold level does not add to a firm value.